WHODUNIT, WHO AM I? FEMINIST AND POSTCOLONIAL IDENTITY IN LAURIE R. KING’S CRIME FICTION - Zahroh, Adiba Qonita (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
Crime fiction has long served not just to entertain but to reflect deeper cultural anxieties about identity, power, and social order. However, its potential to interrogate colonial legacies and gender inequalities remains underexplored. This paper examines how characters from different cultural backgrounds are represented in Laurie R. King’s O Jerusalem, a novel set in British-occupied Palestine, through the combined lenses of postcolonial and feminist theory. Drawing on Edward Said’s concept of Orientalism and Judith Butler’s theory of gender performativity, the study analyses interactions between Western (the Self) and Eastern (the Other) characters, as well as between male and female figures. The aim is to understand how cultural and gendered identities are constructed, contested, and transformed within the context of historical crime fiction. This research contributes to current literature by combining postcolonial and feminist perspectives to address an overlooked intersection in crime fiction studies, how colonial power dynamics and gendered identities are co-constructed and contested within the genre. With the application of this dual framework, the study fills a critical gap in understanding how crime fiction not only reflects but also revises dominant narratives of identity, authority, and resistance. The method involves a careful qualitative analysis grounded in close textual analysis to investigate how identity is constructed and negotiated in O Jerusalem. The analysis focuses on the characterisation of Mary Russell and Sherlock Holmes as Western figures, while also examining how other characters from both Western and Eastern backgrounds are represented. The study pays particular attention to themes of gender, culture, and power as framed by postcolonial and feminist theories. The findings reveal that Laurie R. King complicates cultural and gender identities through evolving relationships between Western and Eastern characters. Her portrayal of Western figures as both protagonists and antagonists challenges the assumed moral superiority of the West. Through Mary Russell, King also redefines female agency in detective fiction by offering a feminist revision of the traditionally male-centred Sherlock Holmes canon. These insights contribute to literary studies by illustrating how popular fiction can critically engage with colonial discourse and gender norms. This dual focus on postcolonial and feminist themes offers fresh insights to rethink detective fiction as a genre that challenges colonial power structures and gender norms. It demonstrates how popular literature can actively contribute to socio-political critique and reshape dominant understandings of identity, culture, and resistance. The study emphasizes the importance of re-evaluating traditional narratives in modern crime fiction.